BELAJAR GEOMETRI DARI SUDUT PANDANG FILOSOFI EPISTIMOLOGI BAGI SISWA SD/MI - Suratiningsih, Suratiningsih; Prasetyo, Sigit (MIDA : Jurnal Pendidikan Dasar Islam, 2024)
Learning geometry from an epistemological philosophy perspective for elementary school students is very important to implement. This research aims to provide an overview of the basic concepts of geometry in the basic education curriculum. Epistemology philosophical theory relevant to geometry learning. The practice of integrating philosophy of epistemology in geometry education for elementary school or Madrasah Ibtidaiyah students. The research method used is a qualitative research method, emphasizing data collection and descriptive data analysis. The data collection method is by collecting and selecting journal articles, books, papers that are relevant to the research topic. Data is collected and analyzed thematically according to relevant topics. The results of the research show that learning geometry is very important for elementary school and Madrasah Ibtidaiyah students. The concept of epistemological philosophy encourages students to think critically. The practice of teaching geometry from an epistemological perspective using activities to explore geometric concepts through sensory experiences is very suitable for elementary school or Madrash Ibtidaiyah students. From this research it can be concluded that this learning is able to help students form attitudes in behavior and critical thinking skills.